2007
DOI: 10.1590/s1415-47572007000400025
|View full text |Cite
|
Sign up to set email alerts
|

Clastogenicity of Piper cubeba (Piperaceae) seed extract in an in vivo mammalian cell system

Abstract: The plant Piper cubeba is widely distributed in tropical and subtropical regions and is used medically for various purposes but has not yet been evaluated for genotoxicity. We used male and female Swiss mice and Wistar rats and the comet assay and micronucleus test to investigate the mutagenic potential of a crude extract of P. cubeba seeds. The rodents were administered 0.5 g kg -1 , 1.0 g kg -1 and 1.5 g kg -1 of the extract by gavage. For the Swiss mice, peripheral blood was collected 24 h after treatment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…On the other hand, crude P . cubeba seed extract was genotoxic in rodents (Junqueira et al ., 2007). Data about the possible mutagenicity or genotoxicity effects from the main components of the above extract have not been reported before.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, crude P . cubeba seed extract was genotoxic in rodents (Junqueira et al ., 2007). Data about the possible mutagenicity or genotoxicity effects from the main components of the above extract have not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding genotoxicity, Junqueira et al . (2007) reported that the crude P . cubeba seed extract was genotoxic in vivo when administered orally to mice and rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters used for statistical analysis were the tail moment and tail length (distance from the middle of nucleoid core to the end of the tail). Cells were visually scored into comet classes according to their tail characteristics: Class 0 = there was no tail, Class 1 = the tail was shorter than the diameter of the head (nucleus), Class 2 = the tail was 1 to 2x the diameter of the nucleus and Class 3 = the tail was longer than 2x the diameter of the nucleus (15)(16)(17). Lack of nucleus in DNA or very wide tailed DNA was deleted from this study because it could be a cell (18,19).…”
Section: Methodsmentioning
confidence: 99%
“…The extent and distribution of DNA damage indicated by comet assay was evaluated by examining cells. The cells were visually scored into comet classes according to tail size class (16, 17, 18) Class 0 = no tail, Class 1 = tail shorter than the diameter of the head (nucleous) , Class 2 = tail length 1 to 2x the diameter of the head and Class 3 = tail longer than 2x the diameter of the head. Comet without head and those with nearly all the DNA in the tail or with a very wide tail, were excluded from the evaluation because they probably represented dead cells (19, 20) tail length and the mutagenic Index were calculated based on the following formula MI = (0NMC+ 1SMC+ 2MMC+ 3LMC) /200, or could be expressed as NMC = No migration cells (score 0), SMC = Short migration cells (score 1) ,MMC = Medium migration cells (score 2), LMC = Long migration cells (score 3).…”
Section: Methodsmentioning
confidence: 99%